Conformational eyelid disorders in dogs under primary veterinary care in the UK - Epidemiology and clinical management - Dan G. O’Neill; Minna P. Mustikka; Dave C. Brodbelt; David B. Church; Vilma Vaattovaara (PLoS ONE, 2025)
Introduction Natural eyelid conformation is essential for normal function and health of the ocular surface. However, many modern dog types are deliberately bred for abnormal eyelid conformation associated with severe health and welfare issues. This study aimed to report the prevalence, demographic risk factors and clinical management under primary veterinary care for conformational eyelid disorders in dogs. Methods The study explored the anonymised clinical records of all dogs under UK primary veterinary care within the VetCompass Programme during 2019. Risk factor analysis used multivariable logistic regression modelling. Results From 2,250,417 dogs under primary veterinary care in 2019, the analysis included a random sample of 3,029 confirmed conformational eyelid disorder cases that included 2,752 (90.86%) entropion and 344 (11.36%) ectropion cases. After accounting for the subsampling process, the annual prevalence for overall conformational eyelid disorder in dogs was 0.36% (95% CI: 0.35–0.37). The annual prevalence for entropion in dogs overall was 0.33% (95% CI: 0.32–0.34). Breeds with highest annual prevalence for entropion were Shar-Pei (15.41%, 95% CI 14.00–16.91), Chow Chow (9.28%, 95% CI 7.64–11.14) and Neapolitan Mastiff (6.88%, 95% CI 3.02–13.14). The estimated annual prevalence for ectropion in dogs overall was 0.04% (95% CI: 0.04–0.05). Breeds with the highest annual prevalence for ectropion were Neapolitan Mastiff (4.30%, 95% CI 1.41–9.77), Saint Bernard (1.72%, 95% CI 0.86–3.05) and Basset Hound (1.59%, 95% CI 0.94–2.49). Surgical management was carried out for 414/2275 (18.20%) of the incident (2019) entropion cases and 12/305 (3.93%) of the incident (2019) ectropion cases. Conclusions Normalisation of conformation-related health issues in certain high profile dog breeds have been discussed as a canine welfare priority for over half a century. The current results suggest that substantial work remains to be done to ensure good innate health for all dogs.